Workfare in Germany and the Problem of Vertical Fiscal Externalities - Holger Feist; Ronnie Schöb (Center for Economic Studies and ifo Institute (CESifo), 1999)
Social assistance to the poor is increasingly subject to compulsory work requirements in Germany. Municipalities have started to offer temporary employment in their job-creation companies to claimants who are able to work. These claimants earn wages and social insurance contributions if they accept the offer, but lose social assistance if they reject it. Further savings to local funds arise from the fact that when a worker's temporary employment ends, he or she is entitled to federal unemployment benefits which involve no costs for the municipality. The paper analyses this vertical fiscal externality and shows that in the long run, municipalities tend to employ a suboptimal number of welfare recipients in their companies.
Keywords: 330; Social assistance; unemployment insurance; fiscal federalism